Surface coating aids survival of Serratia entomophila (Enterobacteriaceae) in granules for surface application. Issue 12 (2nd December 2017) - Wright, David A.; Zydenbos, Sue M.; Wessman, Per; O'Callaghan, Maureen; Townsend, Richard J.; Jackson, Trevor A.; van Koten, Chikako; Mansfield, Sarah
ABSTRACT: The nonspore-forming bacterium Serratia entomophila may be used to control the New Zealand grass grub ( Costelytra giveni ) but is sensitive to environmental stress and must be formulated to improve survival. Existing formulations require subsurface application limiting the area that can be treated. Formulations that allow delivery by broadcast methods are desirable to reduce application costs and increase the potential for aerial application to inaccessible areas. Two formulations were prepared for use in experiments examining the persistence and movement of inoculum through soil. When granules were applied to the soil surface, bacterial survival was negligible in uncoated core, but improved with increasing thickness of the coating. Both survival of bacteria and release into the soil were influenced by soil moisture content. Granules at <12% soil moisture showed high bacterial mortality and reduced delivery to the soil, while at 28% soil moisture most bacteria were released to the soil. There was a high level of survival of the applied bacteria within granules at 20% and 28% soil moisture. The formulations maintained viability of S. entomophila in granules stored under ambient conditions for more than 6 months. In laboratory and field tests, the application of granules caused disease in the target grass grub larvae, whether application was applied to the surface or subsurface. In field trials, broadcast applied granules could produce equivalent disease to thin-coat granules drilled into the soil, but these levels of disease were associated with the occurrence of precipitation shortly after application.